Efficient Generation of Bispecific Murine Antibodies for Pre-Clinical Investigations in Syngeneic Rodent Models - Aran F. Labrijn (Nature Portfolio, 2017)
Abstract Therapeutic concepts exploiting tumor-specific antibodies are often established in pre-clinical xenograft models using immuno-deficient mice. More complex therapeutic paradigms, however, warrant the use of immuno-competent mice, that more accurately capture the relevant biology that is being exploited. These models require the use of (surrogate) mouse or rat antibodies to enable optimal interactions with murine effector molecules. Immunogenicity is furthermore decreased, allowing longer-term treatment. We recently described controlled Fab-arm exchange (cFAE) as an easy-to-use method for the generation of therapeutic human IgG1 bispecific antibodies (bsAb). To facilitate the investigation of dual-targeting concepts in immuno-competent mice, we now applied and optimized our method for the generation of murine bsAbs. We show that the optimized combinations of matched point-mutations enabled efficient generation of murine bsAbs for all subclasses studied (mouse IgG1, IgG2a and IgG2b; rat IgG1, IgG2a, IgG2b, and IgG2c). The mutations did not adversely affect the inherent effector functions or pharmacokinetic properties of the corresponding subclasses. Thus, cFAE can be used to efficiently generate (surrogate) mouse or rat bsAbs for pre-clinical evaluation in immuno-competent rodents.